Clindamycin in the treatment of human infections - Zambrano, David (Michigan Pharmacia & Upjohn, 1997)
The advent of new oral antimicrobial agents that cover gram-negative aerobes, such as the fluoroquinolones.
Keywords: Răng Hàm Mặt